PENGARUH TRANSFORMASI DIGITAL TERHADAP KINERJA KEUANGAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2019-2022) - Sasmita Maharani; Daljono Daljono (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of digital transformation on financial performance by considering firm size. This study uses the dependent variable (financial performance), independent variable (digital transformation), and moderating variables (firm size). This research study uses secondary data gathered from annual reports and financial statements. The population of this study are banking companies listed on the Indonesia Stock Exchange in 2019-2022. By using purposive sampling in sample selection, 104 research samples were obtained for 4 firm-years. This study uses multiple regression analysis to examine the hypothesis. The findings of this study reveal that digital transformation has positive and significant effect on financial performance. Furthermore, it is concluded that firm size moderated effect towards the impact of digital transformation on financial performance.